Peningkatan Kualitas Pengetahuan Hak Kekayaan Intelektual bagi Pengajar Universitas Prasetiya Mulya: Improving the Quality of Knowledge of Intellectual Property Rights for Universitas Prasetiya Mulya Lecturers - Kusmulyono, Muhammad Setiawan (LP2M INSURI Ponorogo, 2022)
The importance of obtaining legal protection of intellectual property rights (IPR) through the registering of creations is yet to be prioritized by univesities in Indonesia. By inviting lecturers to provide understanding, knowledge, and implementation requirements in this IPR registration, the Research Office of Prasetiya Mulya University's School of Business and Economics started the implementation of discussions and socialization of IPR management. Through a qualitative approach by analyzing the activities of virtual discussions, this community service activity seeks to encourage the awareness of stakeholders in higher education to manage intellectual property rights. The benefits of this community service activity ranged from increased teacher awareness and expertise to handling record-keeping concerns, the requirement for assistance in patent preparation, and collaboration procedures with third parties.